2018
DOI: 10.3390/molecules23020396
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Salvia dolomitica and Salvia somalensis Essential Oils against Bacteria, Molds and Yeasts

Abstract: Essential oils (EOs) from Salvia dolomitica and Salvia somalensis, widely employed in the cosmetic and perfume industry, were analyzed for composition and tested against bacterial and fungal pathogens isolated from clinical and environmental specimens. The analyses were carried out against Staphylococcus aureus, Staphylococcus pseudointermedius, Pseudomonas aeruginosa, Escherichia coli, Streptococcus canis, Streptococcus pyogenes, Klebsiella pneumoniae, Proteus mirabilis, Microsporum canis, Microsporum gypseum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In order to get insights about the molecular components of the tested EOs that may act as chemical cues for mosquitoes and the human sensorial system, their chemical composition was characterized by GC-EIMS. The EO profiles of the studied species were completely in agreement with what was previously reported on S. somalensis [33] and S. dorisiana [17]. The S. sclarea EO evidenced results in partial agreement with those observed by Aćimović and co-workers [34] on clary sage EO from Tajikistan.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In order to get insights about the molecular components of the tested EOs that may act as chemical cues for mosquitoes and the human sensorial system, their chemical composition was characterized by GC-EIMS. The EO profiles of the studied species were completely in agreement with what was previously reported on S. somalensis [33] and S. dorisiana [17]. The S. sclarea EO evidenced results in partial agreement with those observed by Aćimović and co-workers [34] on clary sage EO from Tajikistan.…”
Section: Discussionsupporting
confidence: 89%
“…The S. sclarea EO evidenced results in partial agreement with those observed by Aćimović and co-workers [34] on clary sage EO from Tajikistan. The S. dolomitica EO was a subject of discord, in fact, Kamatou et al [35] and Bassolino et al [36] found a composition similar to what we found in the current study, while in a more recent study by Ebani [33], eucalyptol was the main compound. Caser underlined a completely different profile where limonene (19.8%), δ-3-Carene (9.1%), and germacrene D (8.6%) dominated together with (E)-β-ocimene (7.39%) and β-caryophyllene (7.9%) [37].…”
Section: Discussionsupporting
confidence: 89%
“…Geraniol has been tested against C. albicans species and its mechanism of action has been elucidated [21]. Ebani et al [22] have recently demonstrated the activity of five essential oils (star anise, basil, oregano, clary sage and thymus) against multidrug-resistant strains of Escherichia coli , Enterococcus spp., C. albicans and C. famata responsible for urinary tract infections. The pistachio hull essential oil tested in the present work was effective against Candida sp ., whereas polyphenol-rich extracts from pistachios (natural raw shelled and roasted salted pistachios) and white grape juice used in our previous investigations were not effective against yeasts [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Other EOs, such Salvia dolomitica and Salvia somalensis, have been in vitro checked and shown to have poor antidermatophye effects [ 120 ].…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Other studies in vitro concern different Candida species. In detail, C. albicans and C. krusei were shown to be resistant to EOs from S. dolomitica and S. somalensis [ 120 ]. C. krusei from poultry droppings was sensitive to L. cubeba , T. vulgaris , and O. vulgare , as well as C. guilliermondii .…”
Section: Fungal Infectionsmentioning
confidence: 99%